A Cultural Adaptation of Dialectical Behavior Therapy in Nepal. Issue 4 (November 2017) - Ramaiya, Megan K.; Fiorillo, Devika; Regmi, Upasana; Robins, Clive J.; Kohrt, Brandon A.
Abstract: Growing evidence exists on the potential for adapting evidence-based interventions for low- and-middle-income countries (LMIC). One opportunity that has received limited attention is the adaptation of psychotherapies developed in high-income countries (HIC) based on principles from LMIC cultural groups. Dialectical behavior therapy (DBT) is one such treatment with significant potential for acceptability in South Asian settings with high suicide rates. We describe a tri-phasic approach to adapt DBT in Nepal that consists of qualitative interviews with major Nepali mental health stakeholders (Study 1), an adaptation workshop with 15 Nepali counselors (Study 2), and a small-scale treatment pilot with eligible clients in one rural district (Study 3). Due to low literacy levels, distinct conceptualizations of mind and body, and program adherence barriers, numerous adaptations were required. DBT concepts attributable to Asian belief systems were least comprehensible to clients. However, the 82% program completion rate suggests utility of a structured, skills-based treatment. This adaptation process informs future research regarding the effectiveness of culturally adapted DBT in South Asia. Highlights: There is growing public health need to adapt therapies for global mental health settings. Dialectical behavior therapy has strong potential for cross-cultural adaptation. A tri-phasic, collaborative approach was used to adapt DBT for rural Nepali women. Core components of Nepali ethnopsychology were included in the intervention. An 82% program completion rate suggests utility of the adapted program.